The role of scientific evidence in collective action decision-making - Roberts, Ryan, author; Jones, Kelly, advisor; Cottrell, Stuart, advisor; Reid, Robin, committee member; Cheng, Antony, committee member; Duke, Esther A., committee member (Colorado State University. Libraries, 2019)
As our world grows ever more complex, novel forms of governance arise that attempt to manage this complexity. One such governing system is collective action, where multiple stakeholders come together to solve large-scale problems for the benefit of all involved. Collective action is especially prevalent in conservation due to the increased degradation of natural resources, which are often public goods that cross administrative boundaries. Stakeholders whom make collective action decisions typically work with limited resources, and as such it is important they work with adequate information to lead to an increase in efficiency and ultimate success. The growing field of evidence-based conservation highlights this point, which urges practitioners to base their decisions on the best scientific evidence available. The literature repeatedly stresses the importance of information in collective action, yet limited studies exist as to the role of scientific evidence as a specific form of information used in collective action decisions. This dissertation set out to determine this role relative to other factors considered important for success. I drew on the rational decision-making model as a framework for assessing the role of evidence. Using a non-random sample of eight watershed partnerships as a case study, I used a mixed method approach and explored: 1) decision-makers understanding of a specific form of scientific evidence available (Chapter 1), 2) the importance of scientific evidence as a motivation to invest in these watershed partnerships (Chapter 2), and 3) the role of scientific evidence in the partnerships' internal decision-making (Chapter 3). I found that scientific evidence is primarily important to wildfire and forestry specialists regarding decision-making. I also discovered that although evidence is important to internal partnership decision-making, a variety of additional sources of information and other factors that have an equal influence on watershed management exist. The way the watershed partnerships in this study disseminate evidence via outreach strategies was also revealed as a highly important component of success. Synthesizing across these results, I adapted a framework from the literature that incorporates elements of dynamic information pathways that, in conjunction, leads to the long-term success of these eight programs. Some practical considerations for increasing the dissemination and utilization of scientific evidence include translating this type of information into an easily interpretable form and creating web-based tools to organize evidence. Broadly, these results contribute to the collective action literature on the factors necessary in decision-making for the continued endurance of these forms of governance.